2021
DOI: 10.4049/jimmunol.2000792
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Signaling Controls CD155 Expression on Macrophages and Mediates Tumor Immunosuppression

Abstract: Crosstalk between costimulatory and coinhibitory ligands are a prominent node of immune cell regulation. Mounting evidence points toward a critical role for CD155, the poliovirus receptor, in suppressing T cell function, particularly in cancer. However, relative to other known costimulatory/coinhibitory ligands (e.g., CD86, CD80, PD-L1), the physiological functions of CD155 and the mechanisms controlling its expression remain unclear. We discovered that CD155 expression is coregulated with PD-L1 on tumor-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…18 19 A recent study has confirmed higher CD155 messenger RNA expression in TAMs. 20 Similarly, CD155 is overexpressed in CRC tissue and prevents the apoptosis of cancer cells. 21 However, the CD155 expression pattern in CRC TAMs and its role in CRC pathophysiology should still be unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…18 19 A recent study has confirmed higher CD155 messenger RNA expression in TAMs. 20 Similarly, CD155 is overexpressed in CRC tissue and prevents the apoptosis of cancer cells. 21 However, the CD155 expression pattern in CRC TAMs and its role in CRC pathophysiology should still be unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of Interleukin (IL)‐32 was obviously downregulated by Celastrol in HCT116 cells, as well as the expression of CD155 in SW480 cells. Interestingly, some reports proved that IL‐32 (Gruber et al, 2020; Khawar et al, 2017; C. Liu et al, 2020; Ohmatsu et al, 2017; Tsai et al, 2018; Yousif et al, 2013) and CD155 (Huang et al, 2019; Jin et al, 2022; McKay et al, 2021; Noguchi et al, 2019) secreted or expressed by cancer cells were not only regulated by ERK/MAPK signaling pathway but also participated in the process of macrophage polarity regulation, which provided a potential regulatory mechanism of Celastrol on the polarization of macrophages. All these results suggested that ERK/MAPK signaling pathway and related cytokines (e.g., IL‐32) and adhesion proteins (e.g., CD155) may be strongly involved in the regulation process of macrophage polarization by Celastrol in the tumor microenvironment, which needs to be further verified in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In glioblastoma, Kyn produced by cancer cells triggers AhR-signaling to regulate the phenotype of TAMs, and causes the production of adenosine by CD39 and CD73 in TAMs, ultimately leading to CD8 + T cells dysfunction [ 151 ]. In addition, AhR signaling mediates tumor immunosuppression by promoting CD155 expression on TAMs [ 152 ]. CD155, an immune checkpoint as a target for tumor immunotherapy, is universally expressed in solid tumors [ 153 , 154 ].…”
Section: Role Of Ido1 In Tmementioning
confidence: 99%